Fostering critical participatory literacy through policy debate. Issue 3 (13th August 2018) - Cridland-Hughes, Susan; Malloy, Jacquelynn A.; Rogers, Angela
Abstract : Purpose: The purpose of this study is to explore the use of policy debate as a frame for developing critical participatory literacy skills focused on student engagement with current events. Design/methodology/approach: Using dialogism as a frame for a discussion-based course (Bakhtin, 1982; Reznitskya, 2012) and self-study as a methodological structure (Samaras, 2011 ), they explore the iterative process of shaping a policy debate curriculum across three separate cohorts. In the process, they share reflections and insights about what they learned about their assumptions as teachers. Findings: Instructors offer recommendations for structuring literacy practices that are dialogic and focused on student voice and policy activism. Specifically, authors suggest focusing attention to discussion activities, an emphasis on critical dialogue, where students engage with the ideas of others, and the practice of constant facilitator reflection to determine whether they have continued to center student voices and ideas in the classroom. Originality/value: This study is key for beginning to understand how to put students in conversation with complex political decisions and for helping youth develop confidence in their ability to critique and evaluate those decisions as members of the larger society.